Innovative Learning Media Development: Improving Elementary Students’ Speaking Skills with Storytelling-Based Audiovisual Tools - I Made Fendy Agus Gunawan; I Nyoman Laba Jayanta (Universitas Pendidikan Ganesha, 2024)
The development of innovative learning media is essential to improving students' speaking skills. One of the challenges in teaching speaking skills at the elementary school level is the limited use of interactive and engaging media. This study aims to develop a storytelling-based audiovisual medium that is effective in enhancing the speaking skills of sixth-grade elementary school students. The study employed the ADDIE development method, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subject was the storytelling-based audiovisual medium, while the research objects included content validity, media validity, user responses, and media effectiveness. Data were collected through interviews, observations, and questionnaires, using instruments such as observation guidelines, rating scale sheets, interview guides, and questionnaires. The results revealed that the developed medium had a high validity level, with a content validity index of 0.92 and a media validity index of 0.91. The practicality of the medium, based on student responses, reached 97% in the excellent qualification category. The effectiveness test showed that the storytelling-based audiovisual medium significantly improved students' speaking skills, with a significance value (2-tailed) of 0.000, which is less than 0.05. This study concludes that the storytelling-based audiovisual medium is effective in enhancing students' speaking skills in elementary school.